Quality Education Management In Higher Education: A Bibliometric Analysis - Nurlina; Saenab (Indonesian Journal of Educational Research and Review)
Higher education quality is represented by the high standards of knowledge, skills, and values imparted. However, the fact of what still materializes demonstrates it is anything but ideal. This work aimed at examining the quality of higher education deals with describing a more global view on this issue. This study uses bibliometric analysis with data collection based on the Scopus database as the main data source. The optimized analysis tool is Vosviewer. The study's main results show a clear trend in increasing volume of publications on quality higher education since the early 2000s, before reaching its peak level in 2023. The empirical literature on the quality sector remains dominated by contributions from a few countries, predominantly the United Kingdom, the United States, and China. The research further delineates the various hurdles that higher education institutions are up against in fulfilling more exacting quality benchmarks and insists on concerted action be taken to create a conducive learning environment and value-added curricula along with relevant infrastructure. Likewise, these studies also highlight the inherent challenges in pursuing quality education at a national or international level, such us service quality, student satisfaction, teaching, accreditation, e-learning, and sustainable development.